Leaching characteristics of inherent inorganic nutrients in biochars from the slow and fast pyrolysis of mallee biomass - Kong, Zhao Ying; Liaw, Sui Boon; Gao, Xiangpeng; Yu, Yun; Wu, Hongwei (Elsevier Ltd, 2014)
This study compares the inherent leaching characteristics of inorganic nutrients, particularly alkali and alkaline earth metallic (AAEM, mainly Na, K, Mg, and Ca) species in biochars prepared from the slow and fast pyrolysis of mallee biomass particles at 500 C. The results indicate that, compared to slow pyrolysis, fast pyrolysis produces biochars with less water-soluble AAEM species but more plant available AAEM nutrient species (through Mehlich I extraction). Pyrolysis of different biomass components results in biochars with different water-soluble and plant available AAEM nutrient species, depending on pyrolysis conditions. Biochars produced from pyrolysis of large wood particle (2–4 mm) exhibit slower water leaching kinetics and a lower plant available nutrients than those from fine wood particles (150–250 lm). Slow pyrolysis results in a reduction in water-soluble Na and K in biochars while an increment was observed for biochars produced from the fast pyrolysis of large wood. Experimental kinetic data can be broadly fitted to a pseudo-second order model. For all biochars, a significant proportion of inorganic nutrients can be recycled, demonstrating the potential of returning biochar to soil for completing the loop of nutrient recycling and enhancing the sustainability of biomass utilisation cycle.